The social and the economic in social business: Proposition of a conceptual model O social e o econômico em negócios sociais: Proposição de um modelo conceitual - BARBOSA, ALINE DOS SANTOS; MORAES, EDMILSON ALVES; ROMANI-DIAS, MARCELLO (Revista Capital Científico - Eletrônica (RCCҽ) - ISSN 2177-4153, 2017)
This study seeks to analyze how social and economic goals can be balanced in social businesses with the construction of a conceptual model. Through a qualitative approach, proposing a conceptual model based on foundations that characterize the social and economic aspects of social businesses. To teste this model, a data collection instrument was also developed and applied in social businesses. The main finding was that the social businesses analyzed in this study have difficulty balancing their social and economic goals, and tend to concentrate more on one in detriment of the other. As a theoretical contribution, this study makes a contribution to the field by organizing criteria for analyzing this type of enterprise and as a basis for constructing social business measurement scales. As an empirical contribution, this article helps managers in terms of self-evaluation and also to understand how other social businesses address their social and economic goals.